Young children contribute to nature stewardship - Dominguez Contreras, Elena; Krasny, Marianne E. (Frontiers in Psychology, 2022)
Research on young children in environmental education has focused on unstructured play in, or experiencing, nature. Little attention has been paid to young children’s stewardship efforts, or to the relation of such efforts to young children’s learning and capacity to contribute to their communities and local nature. This perspectives paper draws on the first author’s experience guiding pre-k and kindergarten children (4-6 years old) in outdoor educational projects in Santo Domingo, Dominican Republic, in which the children produced a park guide and a short film. In addition to becoming resources for the local community, these products are an example of children’s civic contributions. In “return on investment” language, guiding young children in outdoor experiences and reflecting on the experience represent the investment and the park guide and other products, and importantly, children’s recognition of their ability to make contributions to their community, represent the return on investment. Based on our observations that young children can make significant contributions to their communities when given the opportunity, this perspectives paper argues for a research agenda and investment in opportunities for young children to contribute to their socio-ecological communities. To support our perspective, we first review and critique the prevailing and emerging paradigms of early childhood environmental education, following which we briefly describe the Santo Domingo project, and close by integrating past work with the first author’s experience to argue for the importance of including young children in stewardship efforts.